If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -48 + -5x = 12 + -7x Solving -48 + -5x = 12 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -48 + -5x + 7x = 12 + -7x + 7x Combine like terms: -5x + 7x = 2x -48 + 2x = 12 + -7x + 7x Combine like terms: -7x + 7x = 0 -48 + 2x = 12 + 0 -48 + 2x = 12 Add '48' to each side of the equation. -48 + 48 + 2x = 12 + 48 Combine like terms: -48 + 48 = 0 0 + 2x = 12 + 48 2x = 12 + 48 Combine like terms: 12 + 48 = 60 2x = 60 Divide each side by '2'. x = 30 Simplifying x = 30
| 10-4yi=2x+24i | | 2(-2+x)=x-.875 | | 72/10,000 | | 10(10+c)+2=10 | | 10(10+c)+2=100 | | -14+12x=12+10x | | -5u+14=4u+32 | | 1.5d+3.25=1+2.25s | | 100(10+c)+0=10 | | xsquared-9x=-8 | | 1/3m=33 | | -3u+15=9u-45 | | 6x-30=x+16 | | -83-2x=-10x+93 | | x-1=-2/4x-1/4 | | 4X+17+28=6X | | 5/9=b-1/3 | | 1+5p=11+3p | | -56+3x=5x+80 | | 4(7y-6)-(9y+9)= | | 8(12+9)= | | 6m+2=8 | | a+(-11)=-13 | | 7x+10=210 | | 1+6k+8=-6k+9 | | 6(y-5)-4=20 | | -5x-17=-x-1 | | -8y^2+-5y^2+7y^2+-7y^2= | | (5^-2)x^-1/x^4(y^2) | | n/4-7=5 | | 2x+x(2x+30)=180 | | 4b+10= |